Impact of Shifting China-U.S. Strategic Dynamics on Pakistan’s Geopolitical Positioning - Maimoona Rasool, (Al-Qanṭara, 2024)
The development of Pakistan’s ties with both China and the United States identify crucial turning points and contextualizing them within emerging global power dynamics. It focuses on U.S. primacy and Chinese growing assertiveness, examining Pakistan’s role in the evolving geostrategic environment. The problem of this research is to understand how the intensifying U.S.-China rivalry influences Pakistan’s economy, security and regional standing, particularly in light of key projects like the China-Pakistan Economic Corridor (CPEC). The paper try to find to answer the following questions How does the U.S.-China rivalry shape Pakistan’s strategic decisions and influence its economic cooperation, regional stability and geopolitical positioning? This question is explored through an extensive review of existing literature, with recent works by Zhao and Liu (2024) and Ahmed and Khan (2023) providing essential insights into the ongoing dynamics. However, there remains a gap in understanding how these shifts specifically affect Pakistan. The research employs Realism as its theoretical framework, drawing on the works of Mearsheimer, which emphasizes power competition and strategic interests.to analyze how states struggle for power in an anarchic international system. The research offers nuanced insights into the real- world consequences of major power rivalry on Pakistan’s economic cooperation, regional stability and geopolitical positioning, providing valuable guidance for strategic decision-making in this complex environment